LEGAL PROTECTION AND LOCAL POLICY SUPPORT ON THE COMMERCIALIZATION OF EXPORT PRODUCTS AND INNOVATIVE ADVANTAGES OF MSME PRODUCTS - Purwaningsih, Endang; Muslikh, Muslikh; Suhaeri, Suhaeri; Basrowi, Basrowi (Universitas Galuh, 2024)
The purpose of this study is to describe the direct and indirect effects of legal protection and local policy support on the commercialization of export products and their implications for the innovative advantages of MSME products. The problems explained are (1) the influence of legal protection support and regional policy support on product commercialization, and (2) the role of stakeholders in increasing innovative excellence for product commercialization.The method used in this research is a juridical approach combined with a quantitative approach, sociological especially correlational. This research was conducted in Yogyakarta and Semarang, Central Java, Indonesia. The research population is MSME actors in the two cities, totaling 300 people with a sample of 76 people. Data collection techniques using questionnaires, observation, interviews, and documentation. The quantitative data that has been collected was analyzed using a structural equational modeling (SEM) approach, used Smart PLS software. Qualitative data only used as complementary analysis. The results showed legal protection support and local policy support significantly influenced product commercialization and innovative advantage. Theoretically, this research provides insight into the product commercialization as a mediator variable. With these findings, it is expected that significant support will emerge from the government as a regulator, academics as a educator, the private sector as a catalyst, and the community as a driver for the development of law literacy as MSMEs in Indonesia.